2010
DOI: 10.1017/s0967199410000237
|View full text |Cite
|
Sign up to set email alerts
|

Follicular interactions affect the in vitro development of isolated goat preantral follicles

Abstract: The aim of this study was to evaluate the influence of the number of follicles per drop (one or three) and antral follicles on in vitro development of isolated goat preantral follicles. Preantral follicles were isolated through microdissection and distributed individually (control) or in groups of three follicles (treatment) in microdroplets of α-MEM with or without 1000 ng/ml follicle stimulating hormone (FSH) for Experiments 1 and 2, respectively. Experiment 3 was divided into four treatments according to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…This study has demonstrated that EGF in the presence or absence of FSH increases antrum formation and the diameter of caprine secondary follicles cultured in vitro, suggesting the considerable importance of both substances to follicular development at this stage. In our laboratory, early formation of the antrum has been observed in other experiments (Duarte et al 2010;Silva et al 2010;Araújo et al 2011). Furthermore, we have found that those follicles that do not present a good growth rate and/or slowing process of antrum formation almost always degenerate in the first third of the culture period and that this event is under the direct influence of the follicle size at the beginning of culture.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…This study has demonstrated that EGF in the presence or absence of FSH increases antrum formation and the diameter of caprine secondary follicles cultured in vitro, suggesting the considerable importance of both substances to follicular development at this stage. In our laboratory, early formation of the antrum has been observed in other experiments (Duarte et al 2010;Silva et al 2010;Araújo et al 2011). Furthermore, we have found that those follicles that do not present a good growth rate and/or slowing process of antrum formation almost always degenerate in the first third of the culture period and that this event is under the direct influence of the follicle size at the beginning of culture.…”
Section: Discussionsupporting
confidence: 69%
“…In goats, the isolated follicles contain some stromal tissue around them and several studies Saraiva et al 2010a, b;Magalhães et al 2011;Duarte et al 2010) have shown that these follicles can successfully be cultured directly on plastic. In this system, the vast majority of follicles form an antral cavity after 6 days of culture and the follicular diameter increases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In goats, the rates of MII oocytes grown in vitro is still low compared with those of in-vivogrown oocytes (60%-70% of MII) obtained from antral follicles (Chauan and Anand 1991); the production of mature oocytes from preantral follicles grown in vitro in domestic animals has only been reported in sheep (Tamilmani et al 2005;Arunakumari et al 2007Arunakumari et al , 2010, pigs (Wu et al 2001) and buffalo (Gupta et al 2008). To date, in goat preantral follicles, a low MII rate has been reported (Magalhães et al 2010;Duarte et al 2010). However, we report, for the first time, that the addition of VEGF-A 165 enhances the progression of meiosis to the MII stage, this rate being 29.4% in preantral follicles grown in vitro.…”
Section: Discussionmentioning
confidence: 98%
“…primordial, primary and secondary follicles) that have the potential to be fertilized, but the vast majority becomes atretic during the growth and maturation (Markström et al 2002). To increase the efficiency of this gonad, the role of growth factors and gonadotropins that are involved in the complex bidirectional signaling between the oocyte and the surrounding somatic cells during the growth and development of secondary follicles (~200 µm) up to the antral stage, has been evaluated (Romero and Smitz 2009;Duarte et al 2010;. Oocyte maturation and in vitro embryo production have been described after culture of goat secondary follicles ), but despite the success of these studies, these in vitro systems still have a very low efficiency, with a small percentage of embryos produced from in vitro matured oocytes.…”
Section: Introductionmentioning
confidence: 99%